EasySort App - Mohd Fadzli, Qairunnisa; Junaidee, Syera Nur Alis; Samsudin, Aini Batrisyia; Ghazali, Puteri Syamimi Najihah; Ariffin, Nurul Azrin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Global trade depends on sorting operations in export hubs and warehouses, but manual labelling, handwritten notes and verbal directions are some of the old methods that frequently result in mistakes, delays and lost goods. We created EasySort, a clever sorting tool that uses coloured QR codes to improve item management and to solve these problems. Fast visual identification and precise digital scanning are made possible by the fact that each colour denotes a distinct product category or delivery priority. This dual technique cuts down on new hire training time while increasing sorting speed and accuracy. The EasySort software rapidly recognizes the colour of an item when its QR code is scanned, and it gives clear sorting directions. Additionally, the system minimizes human error and streamlines warehouse operations by tracking sorting actions in real time via a connected platform.